Process intensification for the production of canola-based methyl ester via ultrasonic batch reactor: Optimization and kinetic study - Bokhari, A. (Elsevier, 2020)
Canola oil is an attractive potential feedstock for biofuel production. Great attention has been paid to advanced ultrasonic technology, a potential means to markedly enhance the biodiesel production process through process intensification. In this study, an ultrasonic-assisted batch reactor was employed to investigate the influence of four process parameters, that is, methanol-to-oil molar ratio, catalyst amount, reaction time, and amplitude of ultrasound toward the conversion of methyl esters. In the transesterification reaction for biodiesel production at 60Â°C, a 90wt. methyl ester conversion was achieved in 40min using a 3wt. KOH catalyst and a 6:1 methanol-to-oil molar ratio, which is considered to be remarkably fast compared to conventional methods. Moreover, kinetic study revealed that the transesterification reactions were of pseudo first-order. The activation energy of the transesterification reaction was determined to be 53.717kJ/mol. Â© 2020 Elsevier Inc. All rights reserved.